2017
DOI: 10.2147/ijn.s144623
|View full text |Cite
|
Sign up to set email alerts
|

Aminated nanomicelles as a designer vaccine adjuvant to trigger inflammasomes and multiple arms of the innate immune response in lymph nodes

Abstract: In this study, we suggest a designer vaccine adjuvant that can mimic the drainage of pathogens into lymph nodes and activate innate immune response in lymph nodes. By the amination of multivalent carboxyl groups in poly-(γ-glutamic acid) (γ-PGA) nanomicelles, the size was reduced for rapid entry into lymphatic vessels, and the immunologically inert nanomicelles were turned into potential activators of inflammasomes. Aminated γ-PGA nanomicelles (aPNMs) induced NLRP3 inflammasome activation and the subsequent re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Previous transcriptomic studies of murine models and of post-mortem human ALS tissues also identified upregulation of inflammatory processes 9 , 10 , 13 , 26 , 27 . Inflammasomes are multiprotein complexes that are activated by a variety of factors and induce activation of caspase-1, which mediates production of pro-inflammatory cytokines interleukin-1B and interleukin-18, inducers of pyropoptosis, a highly inflammatory form of programmed cell death 28 . Genes encoding caspase-1 and apoptosis-associated speck-like protein containing a CARD (ASC, also known as PYCARD), which are components of all types of inflammasome complexes, were significantly up-regulated in end-stage PFN1 G118V spinal cords 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous transcriptomic studies of murine models and of post-mortem human ALS tissues also identified upregulation of inflammatory processes 9 , 10 , 13 , 26 , 27 . Inflammasomes are multiprotein complexes that are activated by a variety of factors and induce activation of caspase-1, which mediates production of pro-inflammatory cytokines interleukin-1B and interleukin-18, inducers of pyropoptosis, a highly inflammatory form of programmed cell death 28 . Genes encoding caspase-1 and apoptosis-associated speck-like protein containing a CARD (ASC, also known as PYCARD), which are components of all types of inflammasome complexes, were significantly up-regulated in end-stage PFN1 G118V spinal cords 29 .…”
Section: Discussionmentioning
confidence: 99%
“…AIM2 and NAIP2 transcripts, which are present in AIM2 inflammasomes and NLRC4 inflammasomes, respectively, also were up-regulated in tissues of PFN1 G118V mice at end-stage 29 . The NLRP3 inflammasome complex has been characterized most extensively and implicated in ALS and other neurodegenerative diseases that include Alzheimer’s disease, Parkinson’s disease, frontotemporal dementia, and Huntington’s disease 28 , 30 32 . Investigations of human ALS tissue samples and SOD1 mouse models have shown up-regulation of NLRP3 inflammasome activity 31 , 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies of using this type of nanoparticles for antigen presentation have focused on targeting lymph nodes, based on the rationale that a high density of antigen present cells is present at this location. Smaller nanoparticles (<30 nm) are capable of draining in lymphatic capillaries in a size-dependent fashion (96). In one study, 25 and 100 nm nanoparticles were tested, with a much higher accumulation in dendritic cells seen with the smaller 25 nm particles (97).…”
Section: Biomimetic Nanoparticles For Antigen Presentationmentioning
confidence: 99%
“… 23 25 Activation of the inflammasome through cytosolic NOD-like receptors (NLRs) can lead to a self-adjuvant effect by the nanoparticle vehicle itself that promotes adaptive immunity. 26 28 Lastly, nanoparticles containing vaccines can be used to control the duration of delivery through synchronous and sustained release of antigens and adjuvants. 29 , 30 Delivery kinetics can be further modified using strategies such as incorporating nanoparticles into hydrogels or intradermal microneedle delivery systems.…”
Section: Contemporary Immunoengineering Systemsmentioning
confidence: 99%
“…Furthermore, the targeting of nanoparticles carrying TLR agonists to endosomes leads to activation of endosomal TLRs, promoting strong Th1-type responses (24)(25)(26). Activation of the inflammasome through cytosolic NOD-like receptors can lead to a self-adjuvant effect by the nanoparticle vehicle itself that promotes adaptive immunity (27)(28)(29). Lastly, nanoparticles containing vaccines can be used to control the duration of delivery through synchronous and sustained release of antigens and adjuvants (30,31).…”
mentioning
confidence: 99%